Urocortin in Second Trimester Amniotic Fluid: Its Role as Predictor of Preterm Labor. (15th October 2009) - Iavazzo, C.; Tassis, K.; Gourgiotis, D.; Boutsikou, M.; Baka, S.; Hassiakos, D.; Vogiatzi, C.; Florentin-Arar, L.; Malamitsi-Puchner, A.
Abstract : Backgound . The existence of a "placental clock" which determines the duration of gestation has been previously proposed. It is related to placental CRH secretion and is active from an early phase in human pregnancy. Urocortin is a specific ligand for the corticotropin-releasing factor (CRF) receptor expressed by human trophoblast and fetal membranes. The purpose of this study was to evaluate whether urocortin concentrations in the early second trimester amniotic fluid might serve to predict preterm delivery. Method . The urocortin concentrations in early second trimester amniotic fluid were measured in 41 pregnancies with term delivery and in 41 pregnancies with preterm delivery by using an immunoradiometric assay. Conditional logistic regression analysis was used for statistical analysis. Results . Mean amniotic fluid urocortin concentrations in women with preterm labor were1.55 ± 0.63  ng/mL while those in women with term labor were1.6 ± 0.49  ng/mL (p: NS). No statistical significant results were found when comparing amniotic fluid urocortin concentrations in women with preterm premature rupture of membranes leading to preterm labor (n = 19 ) to women with term delivery without premature rupture of membranes. Conclusion . These results suggest that urocortin concentrations in the amniotic fluid of genetic amniocentesis are not predictive of preterm labor and birth.